An emergency medical care network system for fetal ECG monitoring - Ibrahimy, Muhammad Ibn; Al-Khateeb, Khalid A. Saeed; M. A., Hassan; S. M. A., Motakabber (2011)
Developing and less developing countries (LDCs) are identified in risk of stillbirth due to insufficient emergency medical take-care supports. The regular check-up of the fetal electrocardiography (FECG) could be an earliest prevention of this occurrence. This paper presents a research work aim to implement a simple, customize and portable emergency medical care for the FECG monitoring system from remote location. After acquisitions of the abdominal wall fetal electrocardiography (AFECG) signal from the pregnant mother (patient), the local terminal then transfers this AFECG signal as data to the remote terminal at the expert physician for diagnosis purpose. At the remote terminal, the FECG signals are then extracted from the AFECG signals by our developed software. In this case, computer network establishes a bridge between the patient and a distant expert physician. The network program developed based on the client/server applications. The developed network program is capable to support both the AFECG data transfer and online chat session simultaneously. A specialist physician at the remote terminal can diagnose the FECG signal and provides instruction to the local terminal in case of emergency. A number of cases studied by this developed system and found approximately same result compared with a commercial system.